Outdoor Amphitheater Planning in Mastplan Activities using Autocad 2 D and Sketchup 3 D Applications - Misdar Alamsyah; Muhammad Syarif; Mohd Hazwan (Universitas Negeri Semarang, 2024)
SMK Negeri 1 Sebatik Barat is a school expected to realize SMK Agrotourism, which has a land area of about 35 Hectares. The research